Study on shielded Rogowski coil with return line for measurement of nanosecond-range current pulse. (June 2021) - Yu, Binxiong; Su, Jian-cang; Li, Rui; Zhao, Liang; Cheng, Jie; Zeng, Bo
Highlights: Characteristic of the shielded Rogowski coil also with a return line is studied. Effect of the parasitic line on the output pulse of the coil is analyzed theoretically. A Rogowski coil for high current pulse with rise time less than 4 ns is acquired. Abstract: In this paper, a shielded Rogowski coil aslo with a return line for measurement of the nanosecond-range current pulse is studied. It is found that the connection mode of the end lead has effect on the output pulse waveform of the coil. When the free end of the coil is connected to the ground earth, the output waveform is distorted unless the sampling resistor matches the parasitic transmission line (PTL) formed by the return line and the shielding box. Besides, a prepulse caused by capacitive voltage dividing occurs on the output waveform. However, problems above solved by connecting the free end of the return line to the ground earth. A coil of this kind is developed. It has a turn number over 3000, with a return line of 4-mm diameter. Calibration result of the coil shows that this coil has a flattop jitter of 3% for measurement of the rectangular pulse with a rise time less than 6 ns when its end lead is properly connected. The developed coil is utilized for measurement of the discharge current pulse of a high-voltage pulse generator. Experimental result shows that the coil has good response for the heavy-current pulse with a rise time as fast as 4 ns.